Inovasi Pembelajaran Bebasis Aplikasi Teknologi Dalam Meningkatkan Efektifitas Learning From Home Di Program Studi Pendidikan Ekonomi FKIP UPR - Sundari; Dehen; Sri Rohaetin; Revnussa Octobery; Wenny Awalina (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2021)
The background of this research at the time of the outbreak of the Covid 19 pandemic which required stakeholders to implement an online learning activity system policy or distance learning (PJJ). This study aims to describe the implementation of Learning Innovation Based on Technology Applications in Increasing the Effectiveness of Learning From Home in the Economic Education Study Program FKIP UPR. The benefit of this research is to contribute thoughts, knowledge, information as well as a form of implementation of Technology Application-Based Learning Innovations in Increasing the Effectiveness of Learning From Home in the Economic Education Study Program FKIP UPR. The research method used a descriptive qualitative approach. The data collection techniques were interviews, observation and document study analysis. The results showed a form of online learning innovation developed by lecturers for students of the Economic Education Study Program FKIP UPR, namely that several lecturers stated that online learning made it easier for students to study from home or anywhere using Google Classroom, Zoom Meeting, WhatsApp Group, Google Meet and Youtube. During online learning, several obstacles were found, such as students having different levels of material absorption, unstable internet networks, limited internet quota, power outages, inadequate computer and mobile devices.